THE EFFECTS OF GEOGEBRA ON MATHEMATICS ABSTRACTION: ON ELEMENTARY SCHOOL STUDENTS OF SULTAN AGENG TIRTAYASA UNIVERSITY IN LEARNING GEOMETRY - Mukhtar Mukhtar; Rahmat Firman S; Ujang Jamaludin (JPSD (Jurnal Pendidikan Sekolah Dasar), 2018)
Abstract. Many research indicated that Geogebra has been proven useful as a tool in supporting and transforming teaching and learning. In mathematics classroom, Geogebra can help students and teachers to perform calculation, analyse data, explore mathematical concepts thus increasing the understanding in mathematics. The Geometry learning at the University of Sultan Ageng Tirtayasa, Indonesia, for examining functions and drawing their graphs. In 2017 the authors decided to improve the mathematics abstraction introducing GeoGebra application. This study investigates the effectiveness of using GeoGebra software on Mathematics abstraction among 74 students in Indonesia. This quasi-experimental study with non-equivalent control group post-test only design was conducted to examine the effects of using a free-software called GeoGebra in the learning of Geometry among students classified as Students were divided into two groups of the control group and the experimental group. The control group was given geometry problems to be solved without using GeoGebra. Comparison between those two groups of the Geometry learning, regarding, is described below. Before the Geometry learning, they were tested with a pre-test and their knowledge necessary for examining functions was veriﬁed. The pre-test showed that there was no signiﬁcant statistical difference between the experimental and the control group. Findings of this study showed a significant difference existed in the mean scores between these two  groups. The result indicated that students in the experimental group better than in the control group. Also, GeoGebra enables creation of effective learning environment for examining functions and drawing their graphs.Keyword: Mathematics Abstraction, Geogebra, and Geometry